Identifying the Obstacles of Management Accounting Development in Productive Companies Accepted in Tehran Stock Exchange - Naghi Bahramfar, Ph.D; Shokrolah Khajavi, Ph.D; Amin Nazemi (مجله توسعه و سرمایه, 2008)
In this article, the obstacles of management accounting in productive companies accepted in Tehran stock exchange are studied. The statistical sample is including 52 companies among current industries. The research method is inducting and based on the collected data by means of interview and questionnaire. Hypotheses have been tested using statistical method of Kai 2 distribution. The results indicate that the following 4 factors are of major obstacles in management accounting development of productive companies accepted in Tehran stock exchange.